IRANIAN EFL TEACHERS AND STUDENTS' DEVELOPMENT THROUGH OBSERVATION - Khalil Motallebzadeh; Elham Asa'di (English Review: Journal of English Education, 2013)
Abstract: This paper describes the processes used to examine on one hand the effect of less experienced teachers' participation in experienced teachers' classes on their own skills and teaching methodologies. It also describes the role of teachers' training through observation in their students' achievements. This quasi-experimental design study was conducted In KISH Language School in Bojnurd, Iran. Twenty one EFL teachers were selected as experienced and less experienced ones and involved 169 male and female students (aged 15 - 45 years) as participants. In order to compare students' English proficiency before and after the treatment, a Key English Test (KET) and a Preliminary English Test (PET) were employed. Also, a Peer Observation of Teaching Questionnaire, a sample of TOEFL test and an interview were used to find out the results of teachers' development. This study also revealed that less-experienced teachers' participation in experienced teachers' classes had a significant effect on EFL teachers' skills and strategies used in their classroom and almost all teachers were satisfied with their participation in experienced teachers' classes.Keywords: observation, professional development, less experienced teachers, learners' achievement